Musculoskeletal Disorders (MSD) among Sack Sewing Workers in Duduk Sampeyan District Gresik Regency - Pitaloka, Rizka Dyah; Syamila, Ana Islamiyah; Noveyani, Adistha Eka (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2025)
Musculoskeletal Disorders (MSD) a disorder that cause damage to tissues, muscles, joints, nerves, and bones due to unergonomic working attitudes. Unergonomic work attitudes are often observed among sewing workers. One of the complaints of MSD, low back pain, occupies the highest position in the Gresik Regency in 2023. Sack-sewing workers perform sewing standing; therefore, they often experience leg pain. This study aimed to describe the risk factors for MSD in sack sewing workers in the Duduk Sampeyan District in the production section using a total sampling technique of 39 workers. This type of research uses observational descriptive and descriptive analysis to determine the RR value. Data was obtained from interviews and observations of work posture. The instruments used were Nordic Body Map, Rapid Entire Body Assessment, and %CVL. The results of this study showed that the highest level of pain experienced by workers was in the left leg. The work period showed a tendency towards MSD complaints with a p-value 0.00 and RR 5.8, which means that a working period of > 5 years are 5.8 times more likely to experience MSD than workers with a working period of ≤ 5 years. Although the work posture was not significant, it was in the medium and high categories. Recommendations that can be given are to adjust the height of the sewing table to the worker's anthropometry, stretch during breaks, especially the legs, and form an Occupational Health Post in Duduk Sampeyan District.